Malpernakanan di Kalangan Penduduk Dewasa di Hulu Terengganu - Muda, Wan Abdul Manan (1990)
The assessment of nutritional status of adults was carried out in two villages in Hulu Trengganu in 1982. The aims of the study were to assess the extent of malnutrition among the adult population in the rural areas and to identity socioeconomic variables which could significantly be related to their nutritional status. The study population consisted of 40 males and 67Jemales (N = 107) who were either heads of household or their spouses. The main indicator of nutritional status employed in the study was body mass index of the respondents; however, other anthropometric measurements were also considered. Results of the study indicated that some degree of malnutrition was prevalent in the adult population; 16% of the population under study weighed less than 70% standard and 57.5% of the males weighed less than 80% standard. Based on the body mass index cut off point, it was found that 30.8% of the respondents were malnourishea. Hemoglobin values also show that 38.5% the female respondents suffered from nutritional anemia (n = 62). More than half of the females have hemotocrit values below normal (n = 62). Among the socioeconomic variables which had a significant correlation with nutritional status were education, income and monthly food expenditure.